2023
DOI: 10.1371/journal.pone.0289036
|View full text |Cite
|
Sign up to set email alerts
|

Influence of learning styles on student performance in self-instructional courses

Abstract: This study aimed to analyze the learning style of dentistry students in self-instructional courses to assist in pedagogical planning and to choose the most appropriate educational resources for the students’ learning profile. A sample of 122 students who responded to the Learning Styles Questionnaire was analyzed. For statistical purposes, correlation analysis, chi-square test, odds ratio, and Student’s t-test were performed. In the analyzed sample, there was a higher prevalence of students in the theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Effective studying styles should align with individual strengths, preferences, and learning goals. 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective studying styles should align with individual strengths, preferences, and learning goals. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Effective studying styles should align with individual strengths, preferences, and learning goals. 27 Regarding the students' knowledge of antibiotic use, 25.20% thought that antibiotics are useful against viral infections, including the common cold (32.90%). Similarly, another study in Saudi Arabia showed that 18.1% of medical students thought that antibiotics can be used for viral infections, as did 20% in an Italian study.…”
Section: Discussionmentioning
confidence: 99%
“…Learning styles are the means by which people assimilate information. Literature supports that adapting to learning styles can facilitate effective learning 6 7 .…”
Section: Introductionmentioning
confidence: 99%
“…(2,3,4) Es por este motivo, los estudiantes al encontrarse en esta situación, debieron de generarse otras formas de aprender para enfrentar esta situación, es decir, aprender de manera no presencial implicaba dejar de lado procedimientos propios de la Carrera de Odontología, como son la manipulación, escuchar de manera directa al docente, manipular o ejecutar los recursos en una sesión presencial, por ello exigía a los estudiantes poner en práctica sus diversas maneras de aprender, asimismo sus recursos y estrategias se limitaban a escuchar, observar y hablar; más no así a manipular de manera directa. (5,6) Revisando autores como a Nass et al (7) y Cardoso et al (8) en las Escuelas de odontología y medicina, se debe desarrollar destrezas propias del área, para que así se logre el perfil adecuado, evidenciando que es necesario conocer cuál es el estilo de aprendizaje que poseen, para que así se logre captar la información de manera adecuada e integral, es decir desarrollar habilidades clínicas propias en su formación académica.…”
Section: Introductionunclassified